Comparative Post-conflict Power Sharing Models for Syria - Salamey, Imad (2017)
Salamey, Abu-Nimer, and Abouaoun examine peacebuilding approaches to post-Arab Spring states and compile comparative country analyses derived from different identity politics, nation building, and power sharing models’ experiences in deeply divided societies. This methodology is utilized to induce lessons learned as well as a potential suitable post-conflict power sharing arrangement for Syria. The comparison highlights challenges, opportunities, and prospective options for Syria.